Electrochemical Behaviour of Porous PbO2 Layers Prepared by Oxygen Bubble Templated Anodic Deposition. (10th May 2016) - Comisso, Nicola; Cattarin, Sandro; Guerriero, Paolo; Mattarozzi, Luca; Musiani, Marco; Verlato, Enrico
Graphical abstract: Abstract: Porous PbO2 layers were produced from methanesulfonic acid or perchloric acid media, through an oxygen bubble templated anodic deposition process, i.e. by oxidizing Pb 2+ ions at large current densities, with simultaneous oxygen evolution. The effect of deposition current density, Pb 2+ concentration and nature of the acid on the deposit porosity (assessed through number of pores per unit surface area, average pore diameter, and void volume fraction) were investigated. Porous PbO2 deposits obtained from both media consisted of the same mixture of α- and β-phases, although the corresponding compact deposits had significantly different structures (pure α-PbO2 from methanesulfonic acid, a mixture of α- and β- PbO2 from perchloric acid). The cycling behaviour of compact and porous PbO2 layers in 1.0 M H2 SO4 was compared. During the first cycle, the reduction charge was much higher for porous than for compact layers, as a consequence of the different electrochemically active areas. For the former it depended on the layer thickness, while it was independent of it for the latter. Upon cycling, the charges exchanged by compact layers steadily increased, whereas those of porous layers, after an initial increase, slowly declined, but remained markedly higher.